Understanding the Photodynamic Therapy Induced Bystander and Abscopal Effects: A Review - Kave Moloudi; Paromita Sarbadhikary; Heidi Abrahamse; Blassan P. George (MDPI AG, 2023)
Photodynamic therapy (PDT) is a clinically approved minimally/non-invasive treatment modality that has been used to treat various conditions, including cancer. The bystander and abscopal effects are two well-documented significant reactions involved in imparting long-term systemic effects in the field of radiobiology. The PDT-induced generation of reactive oxygen and nitrogen species and immune responses is majorly involved in eliciting the bystander and abscopal effects. However, the results in this regard are unsatisfactory and unpredictable due to several poorly elucidated underlying mechanisms and other factors such as the type of cancer being treated, the irradiation dose applied, the treatment regimen employed, and many others. Therefore, in this review, we attempted to summarize the current knowledge regarding the non-targeted effects of PDT. The review is based on research published in the Web of Science, PubMed, Wiley Online Library, and Google Scholar databases up to June 2023. We have highlighted the current challenges and prospects in relation to obtaining clinically relevant robust, reproducible, and long-lasting antitumor effects, which may offer a clinically viable treatment against tumor recurrence and metastasis. The effectiveness of both targeted and untargeted PDT responses and their outcomes in clinics could be improved with more research in this area.